2018
DOI: 10.1108/lodj-06-2016-0158
|View full text |Cite
|
Sign up to set email alerts
|

Calling for leadership: leadership relation with worker’s sense of calling

Abstract: Purpose The purpose of this paper is to understand the relation between leadership perception and workers’ sense of calling. Design/methodology/approach Workers’ sense of calling has been shown to relate to organizational outcomes such as job satisfaction, career development, personal growth, and well-being. Although recent studies point the sense of calling as a consequent of several organizational variables, the role of leadership in promoting workers’ sense of calling is yet to be analyzed. A self-report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
3
13
0
2
Order By: Relevance
“…Focusing on individual sense of calling is said to bring advantages to organizations and employees (Dik et al, 2012;Esteves et al, 2018). Employees with a sense of calling tend to have higher job satisfaction, career commitment and perceive more work meaningfulness (Dik et al, 2012;Esteves et al, 2018). Our findings suggested that individuals with a higher sense of calling should be considered as suitable new hires with regard to their career orientation (e.g.…”
Section: Practical Implicationsmentioning
confidence: 78%
See 4 more Smart Citations
“…Focusing on individual sense of calling is said to bring advantages to organizations and employees (Dik et al, 2012;Esteves et al, 2018). Employees with a sense of calling tend to have higher job satisfaction, career commitment and perceive more work meaningfulness (Dik et al, 2012;Esteves et al, 2018). Our findings suggested that individuals with a higher sense of calling should be considered as suitable new hires with regard to their career orientation (e.g.…”
Section: Practical Implicationsmentioning
confidence: 78%
“…work meaningfulness). Taken together, the results indicate that the interactions among variables that affect work meaningfulness may facilitate managerial intervention strategies for employees' well-being and organizational performance in the long run (Esteves et al, 2018).…”
Section: Practical Implicationsmentioning
confidence: 79%
See 3 more Smart Citations